2009
DOI: 10.1007/s00122-009-1151-x
|View full text |Cite
|
Sign up to set email alerts
|

Map-based cloning of the ERECT PANICLE 3 gene in rice

Abstract: Panicle architecture in rice can have a strong influence on yield. Using N-methyl-N-nitrosourea mutagenesis, we isolated an erect panicle mutant, Hep, from Hwasunchalbyeo, a glutinous japonica rice cultivar. Genetic analysis revealed that the erect panicle phenotype was controlled by a single recessive mutation designated erect panicle 3 (ep3). Genetic mapping revealed that the ep3 mutation was located on the short arm of chromosome 2 in a 0.1 cM region delimited by the STS markers STS5803-5 and STS5803-7. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 30 publications
2
67
0
Order By: Relevance
“…And the increased diameter of both culm and panicle may help to enhance the potential in lodging and fertilizer resistance. Genetic studies of erect panicle varieties derived from Balilla and other mutants have identified panicle erectness genes, such as DEP1/qPE9-1, EP2, and EP3, in recent years [10][11][12][14][15][16]. Unlike dep1, the number of spikelets and primary and secondary branches was almost the same in dep2 compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the increased diameter of both culm and panicle may help to enhance the potential in lodging and fertilizer resistance. Genetic studies of erect panicle varieties derived from Balilla and other mutants have identified panicle erectness genes, such as DEP1/qPE9-1, EP2, and EP3, in recent years [10][11][12][14][15][16]. Unlike dep1, the number of spikelets and primary and secondary branches was almost the same in dep2 compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the 'Green Revolution', grain yields have been significantly increased by growing lodging-resistant semi-dwarf varieties of wheat and rice [6,7]. have been reported; EP2 was mapped to chromosome 4, and EP3 encodes a putative F-box protein [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Paraffin-embedded peduncle tissue sections were prepared following the methods described by (Piao et al 2009) with slight modifications. Panicles were harvested at ripening stage.…”
Section: Histological Analysismentioning
confidence: 99%
“…There are several reports on genetic and molecular mechanisms controlling panicle architecture in rice such as DEP1 (dense and erect panicle 1) (Huang et al 2009), DEP2 (dense and erect panicle 2) (Li et al 2010), DEP3 (dense and erect panicle 3) (Qiao et al 2011), EP (erect pose panicle) (Wang et al 2009), EP2 (erect panicle 2) (Zhu et al 2010) and EP3 (erect panicle 3) (Piao et al 2009). DEP1 locus is a gain-of-function mutation causing truncation of a phosphatidylethanolamine-binding protein-like domain protein.…”
Section: Introductionmentioning
confidence: 99%
“…[EP2], EP3) have also been isolated recently (Huang et al, 2009;Piao et al, 2009;Zhou et al, 2009;Zhu et al, 2010). Interestingly, these genes also affect grain shape, although they were originally isolated because of their effect on panicle traits.…”
mentioning
confidence: 99%